Investigation on the exploding foil initiators ignition enhanced by explosion-electricity coupling - Songmao Zhao; Haotian Jian; Ke Wang; Zheng Ning; Peng Zhu; Ruiqi Shen (Defence Technology)
Explosion-electricity coupling (EEC) is a technical method to induce electric energy into the plasma material produced by explosion to improve the output of explosion. Exploding foil initiator (EFI) which could produce plasma during electric explosion can serve as a good carrier for studying the EEC. To investigate the enhancement ability and mechanism of EEC in EFI ignition performance, a kind of EFI chips which could realize the EEC effect was designed and fabricated to observe the characteristics of current and voltage, flyer and plasma temperature during Boron Potassium Nitrate (BPN) ignition of the EFI. It was found that the EEC could enhance EFI ignition in terms of energy utilization, ignition contact surface, and high-temperature sustainability of plasma: firstly, the EEC prolonged the late time discharge (LTD) phase of the electric explosion, making the energy of capacitor effectively utilized; secondly, the EEC could create a larger area of ignition contact surface; last of all, the EEC effect enhanced its high-temperature sustainability by sustaining continuous energy input to plasma. It also was found that the ignition voltage of BPN could be reduced by nearly 600 V under the condition of 0.4 μF capacitance. The research has successfully combined EEC with EFI, revealing the behavioral characteristics of EEC and demonstrating its effective enhancement of EFI ignition. It introduces a new approach to improving EFI output, which is conducive to low-energy ignition of EFI, and expected to take the ignition technology of EFI to a new level.